2020
DOI: 10.1155/2020/3837207
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Larvicidal Activity of Flower Extracts from Clitoria ternatea against Aedes (Diptera: Culicidae)

Abstract: Mosquitoes have always been a human health threat; the major global health problems caused by them are malaria, dengue fever, yellow fever, and Zika as well as several other vector-borne outbreaks. The major problems in controlling these vectors borne diseases are related to resistance to eradication measures. Different classes of insecticides used for controlling public health have raised the concern of resistant problems with mosquitoes and environmental pollution caused by the control measures. Thus, a sear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
(63 reference statements)
4
16
0
Order By: Relevance
“…The dark materials observed in the midgut of the larvae were similar to those observed in previous studies [25,26]. This indicated that the Aedes larvae ingested the V. ovata plant extract, suggesting the killing mechanism of this plant extract against the mosquito larvae.…”
Section: Discussionsupporting
confidence: 87%
“…The dark materials observed in the midgut of the larvae were similar to those observed in previous studies [25,26]. This indicated that the Aedes larvae ingested the V. ovata plant extract, suggesting the killing mechanism of this plant extract against the mosquito larvae.…”
Section: Discussionsupporting
confidence: 87%
“…Toxicity of the crude aqueous extracts in this study were low compared to those of some essential oils reviewed by Pavela (2015), nonetheless, they compared favourably with other plant extracts as indicated earlier (Arjunan et al, 2012;Rawani et al, 2014;Zuharah et al, 2014;Ravindran et al, 2020). In Khater and Shalaby (2008), essential oil of C. esculentus was more efficacious on 4 th instar larvae of Culex pipiens from Egypt compared to the effect of the extracts in this study.…”
Section: Discussionsupporting
confidence: 55%
“…quinquefasciatus, was higher than the response evoked by YDT in both mosquito species. Work by Prathibha et al (2014) and Clitoria ternatea (LC 50 =1 056 mg/L) (Ravindran et al, 2020) on early 4 th instar larvae of Ae. aegypti.…”
Section: Discussionmentioning
confidence: 99%
“…While the other constituents Table 2 which showed unique activity according to the literature like Hexadecanoic acid, methyl ester (Fatty acid ester) [ Ravindran et al, 2020 ], cis -9-Hexadecenal (Long chain unsaturated aldehyde) [50], both of them are larvicidal, cis -Vaccenic acid ( trans -fatty acid) [ Ravindran et al, 2020 ] and 9- Oxononanoic acid (medium-chain fatty acids)[51–52]showing an insecticidal activity, Undecanoic acid a mosquito repellent [ Cantrell et al, 2020 ] while 2-Decenal, (Z)- recorded nematocidal activity [ Caboni et al, 2012 ].…”
Section: Discussionmentioning
confidence: 99%